Fluoroquinolone use and the risk of retinal detachment [Florokinolon kullanimi ve retina dekolmani riski] - (:unkn) unknown (Gazi Eye Foundation, 2014)
An article claiming that oral fluoroquinolone use associates with a high retinal detachment risk has become a hot topic for the last two years. So far, we have five different published important study searching the same issue. Some of them confirmed the first article whilst the others reported contradictory results. The current article aimed to evaluate all those important reports published and summarize this conflicting issue briefly for the readers.
Keywords: Adverse drug effect; Fluoroquinolone; Retinal detachment